Aktualisasi Civic Engagement Melalui Pelayanan Kesehatan di Rumah Sakit PKU Muhammadiyah Karanganyar - Tunjung Bayu Sinta; Harjanti Harjanti (MAN 4 Kota Pekanbaru, 2025)
The low level of patient satisfaction with healthcare services, especially in hospitals, indicates that civic engagement has not been fully implemented. This study aims to explore the actualization of civic engagement and identify the obstacles faced by medical records staff in healthcare services at PKU Muhammadiyah Karanganyar Hospital. This research is motivated by the low level of patient satisfaction with the healthcare services the community receives at the hospital. The method used in this study is a qualitative case study approach to obtain relevant data. Field findings indicate that the implementation of civic engagement at PKU Muhammadiyah Karanganyar Hospital is still limited. The role of the hospital director is crucial in encouraging the implementation of this principle. Some obstacles to this actualization include limited access to the technology used and limited access to health information. Therefore, the hospital director and his staff need to provide motivation and direct role models for hospital staff.